2022
DOI: 10.1186/s12886-022-02247-8
|View full text |Cite
|
Sign up to set email alerts
|

Early and complete vitrectomy versus tap and inject in acute post cataract surgery endophthalmitis presenting with hand motion vision; a quasi-experimental study

Abstract: Background Based on endophthalmitis vitrectomy study, intravitreal injection of antibiotics is preferred for initial management of cases of acute post cataract surgery endophthalmitis (APCE) with presenting vision of hand motions (HM). This study aimed to compare outcomes of early and complete vitrectomy (VIT) and vitreous tap and antibiotic injection (T&I) in cases of APCE presented with vision of HM. Methods In this prospective study, cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…8 Inadequate clearing of bacteria with intravitreal injections alone may be the reason for the need for more reinterventions with T&I. 4,5,12 We noted almost similar improvement in media clarity in both groups at the final follow-up. Again, this could be because almost 40% of the eyes in the initial tap and injection group underwent secondary PPV.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…8 Inadequate clearing of bacteria with intravitreal injections alone may be the reason for the need for more reinterventions with T&I. 4,5,12 We noted almost similar improvement in media clarity in both groups at the final follow-up. Again, this could be because almost 40% of the eyes in the initial tap and injection group underwent secondary PPV.…”
Section: Discussionmentioning
confidence: 68%
“…They noted a significant difference in median gain in the visual acuities between the two groups in favor of early PPV ( P = 0.02). More recently, Tabatabaei et al 5 in a prospective nonrandomized study demonstrated significantly better visual outcomes with early PPV compared with T&I at a 6-month follow-up. This study only included eyes presenting with HM vision, and the results corroborate well with our study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Vitrectomy for endophthalmitis has several advantages for patients, such as removing the infected organism, toxins and the infected vitreous that can cause subsequent retinal detachment [17] . Previous studies have shown that vitrectomy with silicone oil tamponade is preferable for post-surgery endophthalmitis [18][19][20][21] . Complete and early clearance of purulence and toxins is the most critical procedure for endophthalmitis, which will promptly halt and reverse potentially devastating damage to the eyes.…”
Section: Causative Organismsmentioning
confidence: 99%
“…Complete and early clearance of purulence and toxins is the most critical procedure for endophthalmitis, which will promptly halt and reverse potentially devastating damage to the eyes. Complete and early vitrectomy was the initial treatment of choice and recommended by recent studies compared with the tap-and-inject process in the Endophthalmitis Vitrectomy Study (EVS), with 79% of eyes achieving ≥20/40 visual acuity in a recent study compared to 53% in the EVS, especially for those whose initial visual acuity was light perception only [18][19][20][21] . Various factors have been described that influence the prognosis of APCE, such as microorganism virulence and treatment [22][23] .…”
Section: Causative Organismsmentioning
confidence: 99%